2012
DOI: 10.1111/j.1365-2222.2012.03971.x
|View full text |Cite
|
Sign up to set email alerts
|

Specific subcutaneous immunotherapy with recombinant grass pollen allergens: first randomized dose‐ranging safety study

Abstract: The first DBPC SCIT-DRF with a mixture of recombinant Phleum allergens (Phl p 1, 2, 5a, 5b, 6) in patients with rhinoconjunctivitis plus/minus asthma showed no major side effects in very high doses up to 120 μg.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
2
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 35 publications
1
26
2
3
Order By: Relevance
“…Results of trials investigating COPs demonstrated greater improvements in rhinoconjunctivitis symptom scores using 5 injections with 50 μg than with 100 μg ( P = .015) 4, 26. Klimek et al27 reported the highest percentages of CPT response threshold improvements (90% of patients) in the group receiving lower doses of a recombinant 5‐grass pollen SCIT (40 μg) compared to 50% improvement under placebo ( P = .466).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results of trials investigating COPs demonstrated greater improvements in rhinoconjunctivitis symptom scores using 5 injections with 50 μg than with 100 μg ( P = .015) 4, 26. Klimek et al27 reported the highest percentages of CPT response threshold improvements (90% of patients) in the group receiving lower doses of a recombinant 5‐grass pollen SCIT (40 μg) compared to 50% improvement under placebo ( P = .466).…”
Section: Discussionmentioning
confidence: 99%
“…Fifty per cent of control group patients in the study by Klimek et al exhibited decreased CPT reactivity after receiving placebo. The authors argued that post‐treatment reprovocations at threshold doses from baseline (without prior up‐dosing and less cumulative allergen) were a possible cause 27. Jutel et al1 were unable to demonstrate significantly different CPT results between placebo and actively treated groups, with 53.8% of the placebo group patients having higher CPT response thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…It is more effective with perennial rather than with preseasonal conditioning although the safety profile is similar [82]. No major side effects have been reported with doses as high as 120 mg [83]. It has been shown to be more effective than topical treatment both in terms of subjective symptoms and objective inflammation (serum immunoglobulin IgE) in VKC [84].…”
Section: Immunotherapymentioning
confidence: 99%
“…Entwicklungen im Bereich von rekombinanten Wildtypallergenen und hypoallergen modifizierten Allergenen sowie im Bereich der Peptidtherapie scheinen vielversprechend [35,36]. Rekombinante Allergene wurden erstmals im Jahre 1988 hergestellt [37,38].…”
Section: Individualisierung In Der Allergologie: Spezifische Immuntheunclassified